A comprehensive review on the ethnobotany, phytochemistry, pharmacology and quality control of the genus Lycium in China. Issue 7 (13th March 2023) - Yu, Zhonglian; Xia, Mengqin; Lan, Jiping; Yang, Li; Wang, Zhengtao; Wang, Rui; Tao, Hongxun; Shi, Yanhong
Abstract : The distribution, botanical features, and chemical compounds of the Lycium genus in China, as well as the pharmacological effects and international quality control of Lycium fruits, are comprehensively reviewed. Abstract : The Lycium genus, perennial herbs of the Solanaceae family, has been an important source of medicines and nutrient supplements for thousands of years in China, where seven species and three varieties are cultivated. Among these, Lycium barbarum L. and Lycium chinense Mill., two "superfoods", together with Lycium ruthenicum Murr, have been extensively commercialized and studied for their health-related properties. The dried ripe fruits of the genus Lycium are well recognized as functional foods for the management of various ailments including waist and knee pain, tinnitus, impotence, spermatorrhea, blood deficiency and weak eyes since ancient times. Phytochemical studies have reported numerous chemical components in the Lycium genus, categorized as polysaccharides, carotenoids, polyphenols, phenolic acids, flavonoids, alkaloids and fatty acids, and its therapeutic roles in antioxidation, immunomodulation, antitumor treatment, hepatoprotection and neuroprotection have been further confirmed by modern pharmacological studies. As a multi-functional food, the quality control of Lycium fruits has also attracted attention internationally. Despite its popularity in research, limited systematic and comprehensive information has been provided on the Lycium genus. Therefore, herein, we provide an up-to-date review of the distribution, botanical features, phytochemistry, pharmacology and quality control of the Lycium genus in China, which will provide evidence for further in-depth exploration and comprehensive utilization of Lycium, especially its fruits and active ingredients in the healthcare field.